Distribution of Mycobacterium leprae Strains among Cases in a Rural and Urban Population of Maharashtra, India - Kuruwa, Sanjana (American Society for Microbiology, 2012)
The elimination of leprosy continues to be a challenge, with the disease remaining endemic in several countries. India accounts for the highest number of cases, and the identification of child cases indicates recent transmission. Genetic markers, like variable-number tandem repeats (VNTRs) and single-nucleotide polymorphisms (SNPs), have been identified to track transmission of the pathogen Mycobacterium leprae. They were used to describe M. leprae strains detected in 48 skin biopsy specimens from leprosy patients in the state of Maharashtra in western India in rural and urban areas near Mumbai. Ninety-three percent of strains across both settings belonged to the SNP type 1D, with three of SNP type 1B being identified in patients living within 3 km of each other. The VNTR profiles of the Maharashtra strains clustered with those from Southern India reported previously and a few other Asian strains, indicating that the Indian strains are genotypically conserved at the level of many VNTR loci. Taken together, SNP and VNTR markers are sufficiently reliable and suitable for both localized and broad geographical genotype associations. VNTR profiles of additional cases may aid in distinguishing the SNP type 1B and 1D strains.